PENDIDIKAN KESEHATAN REPRODUKSI MELALUI VIDEO EDUKASI KEPADA REMAJA - Wahyudi, Gufron; Raharjo, Rahmawati (Stikes Yarsi Mataram, 2024)
Teenagers aged 10-24 often face limited access to reproductive health information. Societal taboos, particularly towards women, complicate issues such as sexuality, HIV/AIDS, drugs, and relationships. In response, an educational initiative using video was implemented for 10th-grade students at SMK Puspa Bangsa Cluring Banyuwangi. Activities involved socialization, discussions, and simple interviews. Evaluation revealed a significant improvement in adolescents' understanding, increasing from 70% to 90% post-education. The positive response from teenagers towards the educational videos reflects the success in delivering engaging and effective information. The research concludes the effectiveness of the video-based educational approach. With adjustments, this program has the potential to serve as a model for similar activities in the future, involving schools, families, and communities holistically.